Blueprint for success in college : career decision making - Dillon, Dave; Hill, Linda Bruce; Rebus Community; Lumen Learning; BC Open Textbook Project; BCcampus ([Rebus Community Press], 2018)
"Blueprint for Success in College: Career Decision Making is a students' guide for the process of identifying a major and career. This text focuses on career exploration. This book is a remix of two previously existing OER (Open Educational Resources): Foundations of Academic Success: Words of Wisdom, edited by Thomas Priester, and College Success, provided by Lumen Learning. The Blueprint for Success series comprises three books for the College Success and FYE (First-Year Experience) genre. The central text, Blueprint for Success in College and Career, is designed to show how to be successful in college and in career preparation. In addition, targeted sections on Study Skills and Time Management, and Career and Decision Making are available separately as Blueprint for Success in College: Indispensable Study Skills and Time Management Strategies, and Blueprint for Success in Career Decision Making."--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Description based on online resource; title from PDF title page (viewed on July 23, 2018).
Keywords: Vocational guidance -- Textbooks; Electronic books